Genetic variants of alcohol‐metabolizing enzymes in Brugada syndrome: Insights into syncope after drinking alcohol. Issue 5 (19th August 2019) - Wu, Qi; Hayashi, Hideki; Hira, Daiki; Sonoda, Keiko; Ueshima, Satoshi; Ohno, Seiko; Makiyama, Takeru; Terada, Tomohiro; Katsura, Toshiya; Miura, Katsuyuki; Horie, Minoru
Abstract: Background: Patients with Brugada syndrome (BrS) are known to have arrhythmic events after alcohol drinking and are recommended to avoid its excessive intake. Mechanisms underlying the alcohol‐induced cardiac events are however unknown. This study aimed to test the hypothesis whether activity of alcohol‐metabolizing enzymes determines fatal arrhythmic events after drinking alcohol. Methods: A total of 198 Japanese patients with BrS were enrolled in this study. These patients were classified into symptomatic (n = 90) and asymptomatic (n = 108) groups. The former was divided into an alcohol‐related group (syncope after alcohol drinking, n = 16) and an alcohol‐unrelated group (n = 74). Polymerase chain reaction was performed to determine genetic variants of genes encoding alcohol dehydrogenase 1B ( ADH1B ) and aldehyde dehydrogenase 2 ( ALDH2 ). Results: The genotype distribution for ALDH2 was not significantly different between symptomatic and asymptomatic groups and between alcohol‐related and alcohol‐unrelated groups. The genotype distribution for ADH1B was not significantly different between symptomatic and asymptomatic groups, but the genotype ADH1B His/His was significantly more prevalent in the alcohol‐related group than in the alcohol‐unrelated group (81.3% vs 50%, P  = .023). In multivariate logistic regression analysis, the genotype of ADH1B His/His was independently associated with syncope after alcohol drinking (odds ratio, 5.746; 95% confidence interval, 1.580‐28.421; P  = .007). Conclusions: Arrhythmic events after alcohol drinking was associated with enhanced activity of alcohol‐metabolizing enzyme ADH1B in our cohort of BrS. Therefore, the lifestyle change to avoid the excessive alcohol intake deserves attention. Abstract : Arrhythmic events after alcohol drinking was associated with enhanced alcohol metabolism resulting from ADH1B gene variant (His47His) in our cohort of Brugada syndrome. Lifestyle change to avoid the excessive alcohol intake may therefore deserves attention.